Unlocking Business Performance through Artificial Intelligence Adoption: The Role of Innovation Capability in Technopreneurship - Arif Rachmat Darmawan; Eddy Soeryanto Soegoto; Ganieva Nasiba Shukhrat Kizy (International Journal of Entrepreneurship & Technopreneur (INJETECH), 2026)
Artificial Intelligence (AI) is continuing as a technology with strategic importance for the improvement of competitiveness of small and medium-sized enterprises (SMEs). However, the ways by which AI is creating value for business are not fully clarified. The present study brings forward a conceptual system, where it describes how the adoption of AI is influencing business performance by means of innovation capability in SMEs of Indonesian technopreneurs. A systematic review of literature was carried out through examination of latest investigations concerning AI adoption, innovation capability, business performance, as well as technopreneurship. Insights were synthesized from Resource-Based View (RBV), Dynamic Capability Theory (DCT), and also from the Technology–Organization–Environment (TOE) framework. The framework that has been proposed indicates AI adoption by itself does not sufficiently lead to improvement in business performance. This can only occur when companies encounter development of organisational capability for transforming technological resources into innovation. This theoretical viewpoint indicates that the capability of innovation serves as the strategic system, which connects adoption of AI to sustainable performance in businesses. It does this through the integration of dimensions technological, organisational, as well as environmental.